2014
DOI: 10.1021/jf503840d
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Allelopathic Interaction Between Rye and Wild Oats

Abstract: Allelopathy is a biological phenomenon in which an organism produces one or more biochemicals that influence the growth, survival, and reproduction of other organisms. Allelopathy has been the subject of a great deal of research in chemical ecology since the 1930s. The characterization of the factors that influence this phenomenon has barely been explored, mainly due to the complexity of this area. The main aim of the research carried out to date has been to shed light on the importance of these interactions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 37 publications
(66 reference statements)
2
51
0
Order By: Relevance
“…The presence of these allelochemicals in the rhizosphere depends on factors such as species, cultivar, or plant density (Huang et al, 2003;Belz and Hurle, 2005;Macías et al, 2014). Maybe the best estimate for naturally occurring APO concentrations can be gained from studies of exudation of the APO precursor DIBOA from roots: In hydroponic cultures, DIBOA released from rye (Secale cereale) and durum (Triticum durum) roots accumulated to concentrations of 300 and 30 µM, respectively (Belz and Hurle, 2005;Macías et al, 2014). Given the equimolar conversion of DIBOA to BOA, and a conversion rate of 10:1 of BOA into APO (Gents et al, 2005;Understrup et al, 2005), this would result in APO concentrations of 30 and 3 µM, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of these allelochemicals in the rhizosphere depends on factors such as species, cultivar, or plant density (Huang et al, 2003;Belz and Hurle, 2005;Macías et al, 2014). Maybe the best estimate for naturally occurring APO concentrations can be gained from studies of exudation of the APO precursor DIBOA from roots: In hydroponic cultures, DIBOA released from rye (Secale cereale) and durum (Triticum durum) roots accumulated to concentrations of 300 and 30 µM, respectively (Belz and Hurle, 2005;Macías et al, 2014). Given the equimolar conversion of DIBOA to BOA, and a conversion rate of 10:1 of BOA into APO (Gents et al, 2005;Understrup et al, 2005), this would result in APO concentrations of 30 and 3 µM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting product APO is a highly potent phytotoxin, which is also the case, although to a lesser extent, for AMPO (Macías et al, 2006(Macías et al, , 2009. The allelochemicals APO and AMPO as well as their precursors have been detected in plants in proximity to DI(M)BOA donor plants (Macías et al, 2014).…”
Section: Docking Simulation Of Apo and Ampo To Hdacsmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, scientific progress and new equipment and experimental protocols have helped to reveal parts of this complex problem. Some allelochemicals, such as benzoxazinones and their derivatives, which can cause weed suppression, have been already characterized from their production in the donor plant (Secale cereale L.) to their action on the target plant (Avena fatua L.) (Macías et al 2014). Up to 20 kg ha -1 benzoxazinones can be released from rye residues and after degradation, up to 5 kg ha −1 was recovered from the soil .…”
Section: The Use Of Allelopathy In Cropping Systemsmentioning
confidence: 99%
“…Experiments on durum wheat and rye showed that DIBOA accumulated in the leachate at concentrations of 30 mM and 300 mM, respectively. 7,8 Taking into account a 10:1 conversion rate of DIBOA to APO, 9,10 the resulting APO concentration reaches 3 mM to 30 mM. In our previous experiments we had determined the half-maximal-effect concentration (EC 50 ) of APO to be 75 mM, 2 and thus slightly above the concentrations found in the root leachates.…”
mentioning
confidence: 99%